Karakter Tokoh Kancil dalam Serat Dongeng Anyariyosaken Lelampahanipun Kancil Tedhakan Raden Mas Dayat Mukadam Nataseputra - Aji, Wahyu Rintoko; Wijayanti, Kenfitria Diah; Fitriana, Tya Resta (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2023)
The goal of this study is to look at Serat Dongeng Anyariyosaken Lelampahanipun Kancil tedhakan Raden Mas Dayat Mukadam Nataseputra as an example of instilling character education values that can be applied in everyday life. This Serat follows Kancil from his birth to the end of his life. This Serat is interesting to study because it contains many character development values demonstrated by the character Kancil. The data used in this study are phrases, clauses, and sentences from Serat Dongeng Anyariyosaken Lelampahanipun Kancil that demonstrate character education. The data analysis technique used is data collection, data reduction, data writing, and conclusion drawing. This study took a descriptive qualitative approach. The results of the study show that the Kancil character has good characters that can be emulated, including 1) honesty; 2) religious; 3) creativity; 4) democratic; 5) peace; and 6) social care. Keywords: Serat Dongeng Anyariyosaken Lelampahanipun Kancil, Character education, Kancil